Exopolysaccharides-Producing Lactic Acid Bacteria in Marinated Pakoba (Syzygium luzonense Merr.) Fruit - Revanda Stevanie Hasani; Helen Joan Lawalata; Anita Constanci Christine Tengker; Marthy Stella Taulu; Fernando Andre Watung (Institute for Research and Community Services Udayana University (LP2M Universitas Udayana), 2025)
Pakoba fruit is one of the endemic flora of North Sulawesi which is rich in nutrients and has the potential to be fermented. The fermentation process occurs due to the bacteria in the fruit, including lactic acid bacteria (LAB). One of the interesting products from LAB fermentation is that it can produce secondary metabolites which have the potential to produce exopolysaccharides, namely high molecular weight and biodegradable polymers. This research aims to determine whether LAB can be obtained from fermentation of Pakoba marination and what types of LAB produce exopolysaccharides based on their phenotypic characteristics. This research uses a qualitative descriptive method to characterize the type of LAB and observe the exopolysaccharides produced by the bacteria. This research succeeded in isolating and identifying 10 LAB isolates based on their morphological and biochemical characters. Four isolates named MP(1)5.2, MP(1)7.1, MP(3)6.3, MP(3)7.2 can produce exopolysaccharides with a soft character but not mucus, where bacterial exopolysaccharides are believed to increase probiotics in the digestive tract. Genus level recognition (generic assignment) based on profile matching revealed that these four bacteria were from the genus Lactobacillus.